1999
DOI: 10.1590/s0100-879x1999000700015
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alterations in head and neck squamous cell carcinomas

Abstract: The genetic alterations observed in head and neck cancer are mainly due to oncogene activation (gain of function mutations) and tumor suppressor gene inactivation (loss of function mutations), leading to deregulation of cell proliferation and death. These genetic alterations include gene amplification and overexpression of oncogenes such as myc, erbB-2, EGFR and cyclinD1 and mutations, deletions and hypermethylation leading to p16 and TP53 tumor suppressor gene inactivation. In addition, loss of heterozygosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…Interestingly, we found a signi®cant association of p16 INK4a promoter methylation and younger age of smoking initiation in HNSCC. This supports other studies that suggest p16 INK4a methylation to be an early event in solid tumors that can be detected in precursor lesions, or dysplasia (Nagai, 1999;Belinsky et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, we found a signi®cant association of p16 INK4a promoter methylation and younger age of smoking initiation in HNSCC. This supports other studies that suggest p16 INK4a methylation to be an early event in solid tumors that can be detected in precursor lesions, or dysplasia (Nagai, 1999;Belinsky et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…The inactivation of the p16 INK4a gene is common in HNSCC and plays an important role in tumor development (Esteller et al, 2001;Reed et al, 1996;Sanchez-Cespedes et al, 2000;Riese et al, 1999;Nagai, 1999). We have previously shown that tobacco carcinogen exposure is associated with methylation of the p16 INK4a gene in lung cancer (Kim et al, 2001a).…”
Section: Introductionmentioning
confidence: 88%
“…Over the last decade, scientific research related to these events has been performed to investigate biological, diagnostic, and prognostic parameters. [3][4][5][6][7][8] These include growth factors and their receptors, signal transducers, transcription factors, cell cycle regulators, p53, proliferative and apoptotic proteins, cyclooxygenase 2, nuclear factor kappa B, hypoxia-related proteins, and angiogenesis. [3][4][5][6][7][8] In head and neck cancer, except for epidermal growth factor receptor (EGFR), there are few studies that have correlated the protein expression of signal transducer and activator of transcription 3 (Stat3), c-myc, and H-ras with clinicopathologic parameters.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8] These include growth factors and their receptors, signal transducers, transcription factors, cell cycle regulators, p53, proliferative and apoptotic proteins, cyclooxygenase 2, nuclear factor kappa B, hypoxia-related proteins, and angiogenesis. [3][4][5][6][7][8] In head and neck cancer, except for epidermal growth factor receptor (EGFR), there are few studies that have correlated the protein expression of signal transducer and activator of transcription 3 (Stat3), c-myc, and H-ras with clinicopathologic parameters. [9][10][11][12][13][14][15] Furthermore, in OSCC, most of the studies pertain to components associated with the 2 well-defined cell cycle regulatory pathways (Rb and p53 pathways).…”
mentioning
confidence: 99%
“…Over the last decade, scientific research related to the specific pathways which are relevant to the development and progression of this disease has been performed to investigate biological, diagnostic and prognostic parameters. [7][8][9][10] DNA damage is one of the underlying causes for mutations which is very numerous and appears to be a fundamental problem for life leading to cancer. In human cells, the estimated average number of DNA damages occurring per hour is about 800 which reach to 19,200 per day.…”
Section: Introductionmentioning
confidence: 99%